Computational Study of Phytopharmaceutical Antidiabetes Potential of Gorontalo Traditional Medicine Plants - La Kilo, Akram; Aman, La Ode; Asisah, Asisah; Ischak, Netty Ino; Paputungan, Mardjan; Alio, La (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2023)
Diabetes Mellitus (DM) was a disease characterized by the occurrence of hyperglycemia. This study aimed to analyze the activity of compounds in traditional medicinal plants as potential anti-diabetic candidates using the MM method and to analyze the interactions of compounds contained in traditional medicinal plants that could be used as anti-diabetic drugs. The methods used were Molecular docking and Molecular dynamics, with the Aldose reductase 2HV5 receptor and the ligand ZST. Based on the research findings, the active compounds identified as potential anti-diabetic drugs were Calebin_A and alpha_tocotrienol. Docking method validation on Protein 2HV5 using the natural ligand ZST showed an RMSD of 0.66 Å. The best results from molecular docking were obtained with Calebin_A, which had a binding affinity of -11.3 kcal/mol, and alpha_tocotrienol, which had a binding affinity of -11.2 kcal/mol. The results of the molecular dynamics method on the best complexes were evaluated by considering the changes in system energy, system temperature, pressure, RMSD, RMSF, and binding free energy (∆G). The standard ligand ZST had a value of -30.43 kcal/mol, the test ligand calebin_A had a value of -34.48 kcal/mol, and alpha_tocotrienol had a value of -39.46 kcal/mol.